PENINGKATAN PEMAHAMAN MEMBACA MENGGUNAKAN KARTU BACA PADA SISWA KELAS II SD NEGERI 1 SEMBOWO - Dwi Cahyono Dewo; Hartini Hartini; Sutiman Sutiman (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2023)
The reading ability of students at SDN 01 Sembowo varies, ranging from not being able to read at all or being able to read but not fluent. This problem occurs because it comes from the students themselves and also the lack of attention from parents in guiding them at home. Even in the classroom, there is actually reinforcement or assistance in reading, but students are not able to accept it well. Classroom action research was used in this study with the planning, implementation (action) and evaluation reflection stages. Observation and tests are used as data collection techniques. The research was conducted in stages through two cycles. In this study, the average post-procedure yield in Cycle II was 75%, which was an increase compared to Cycle I, which was only 62.5%. This can be strengthened by increasing students' reading literacy, which causes students to become more active and learn with more confidence in themselves. The advice given is that teachers should be able to optimize all available resources so that they can boost teacher creativity and quality.